Collaborative Governance in Driving MSME Technology Adoption for Smart Economy Acceleration in Yogyakarta - Awang Darumurti; Helen Dian Fridayani; Muhammad Eko Atmojo; Li Chun Chiang (Journal of Government and Civil Society, 2025)
This research examines the role of Collaborative Governance in encouraging technology adoption by MSMEs to accelerate the smart economy in Yogyakarta. MSMEs have a strategic role in the regional economy, but still face obstacles in digitalization. The Collaborative Governance approach was chosen because it allows active involvement of various stakeholders in supporting the digital transformation of MSMEs. The method used is qualitative with a case study approach. Data were obtained through interviews with the DIY Cooperative and SME Agency and Bapperida, as well as analysis of relevant documents. Data analysis was conducted using interactive model techniques and Nvivo 12 Plus software. The results show that collaboration between the government, private sector, and the MSME community plays an important role in providing digital infrastructure, training, and support for programs such as SiBakul. This process takes place through three main stages: (1) identification of barriers and opportunities, (2) formulation of digitalization strategies, and (3) implementation of technology-based programs. In technology adoption, the highest indicators are perceived benefits and ease of use, indicating MSMEs' awareness of the benefits of technology. Although MSME awareness is high, technology implementation is still constrained in intention and actual use.Penelitian ini mengkaji peran Tata Kelola Kolaboratif dalam mendorong adopsi teknologi oleh UMKM untuk mempercepat perekonomian cerdas di Yogyakarta. UMKM memiliki peran strategis dalam perekonomian regional, namun masih menghadapi hambatan dalam proses digitalisasi. Pendekatan Tata Kelola Kolaboratif dipilih karena memungkinkan keterlibatan aktif berbagai pemangku kepentingan dalam mendukung transformasi digital UMKM. Metode yang digunakan adalah kualitatif dengan pendekatan studi kasus. Data diperoleh melalui wawancara dengan Badan Koperasi dan UMKM DIY dan Bapperida, serta analisis dokumen-dokumen terkait. Analisis data dilakukan menggunakan teknik model interaktif dan perangkat lunak Nvivo 12 Plus. Hasil menunjukkan bahwa kolaborasi antara pemerintah, sektor swasta, dan komunitas UMKM memainkan peran penting dalam menyediakan infrastruktur digital, pelatihan, dan dukungan untuk program seperti SiBakul. Proses ini berlangsung melalui tiga tahap utama: (1) identifikasi hambatan dan peluang, (2) formulasi strategi digitalisasi, dan (3) implementasi program berbasis teknologi. Dalam adopsi teknologi, indikator tertinggi adalah manfaat yang dirasakan dan kemudahan penggunaan, menunjukkan kesadaran UMKM akan manfaat teknologi. Meskipun kesadaran UMKM tinggi, implementasi teknologi masih terkendala dalam niat dan penggunaan aktual.